Social representations of labor for assisted of prison system of Ceará (Research, Society and Development, 2021)
To know the social representations of the work for the assistants of the prison system of Ceará, its forms of insertion and expectations in relation to the work contexts was the objective of this research. Twenty-three assistants, who were residents of Fortaleza, participated in the work of the Secretariat of Justice and Citizenship of the State of Ceará (Sejus). Data were collected through semi-structured interviews and submitted to content analysis. The results evidenced work as a necessary condition for freedom (material, personal / affective and social), as well as for the construction of a new sociability. Emphasis is given to aspects that make it difficult for the prison system to participate in the labor market, such as personal and social barriers. It is concluded that social representations guide social practices and strategies, reflecting the norms of social institutions or the ideologies related to the place that the assistants occupy in society.